Splenectomy before allogeneic hematopoietic cell transplantation for myelofibrosis: A French nationwide study. Issue 1 (18th November 2020) - Bossard, Jean‐Baptiste; Beuscart, Jean‐Baptiste; Robin, Marie; Mohty, Mohamad; Barraco, Fiorenza; Chevallier, Patrice; Marchand, Tony; Rubio, Marie‐Thérèse; Charbonnier, Amandine; Blaise, Didier; Bay, Jacques‐Olivier; Botella‐Garcia, Carmen; et al.
Abstract: The value of pretransplant splenectomy in patients with myelofibrosis (MF) is subject to debate, since the procedure may preclude subsequent allogeneic hematopoietic cell transplantation (allo‐HCT). To determine the impact of pretransplant splenectomy on the incidence of allo‐HCT, we conducted a comprehensive retrospective study of all patients with MF for whom an unrelated donor search had been initiated via the French bone marrow transplantation registry (RFGM) between 1 January 2008 and 1 January 2017. Additional data were collected from the patients' medical files and a database held by the French‐Language Society for Bone Marrow Transplantation and Cell Therapy (SFGM‐TC). We used a multistate model with four states ("RFGM registration"; "splenectomy"; "death before allo‐HCT", and "allo‐HCT") to evaluate the association between splenectomy and the incidence of allo‐HCT. The study included 530 patients from 57 centers. With a median follow‐up time of 6 years, we observed 81 splenectomies, 99 deaths before allo‐HCT (90 without splenectomy and nine after), and 333 allo‐HCTs (268 without splenectomy and 65 after). In a bivariable analysis, the hazard ratio [95% confidence interval (CI)] for the association of splenectomy with allo‐HCT was 7.2 [5.1‐10.3] in the first 4 months and 1.18 [0.69‐2.03] thereafter. The hazard ratio [95% CI] for death associated with splenectomy was 1.58 [0.79‐3.14]. These reassuring results suggest that splenectomy does not preclude allo‐HCT in patients with MF.